Telecom license fees & risks in sub-Saharan Africa - (:unkn) unknown (My University, 2013)
Disparities in telecom license fees between countries might lead to skepticism of investors about the "real" value of a license and to reluctance to apply for those. This paper introduces a preliminary study on the relationship between license prices and host country environment in the African mobile sector. It is based on an original database that includes all mobile licenses acquisitions by the twelve biggest multinational operators that have invested in sub-Saharan Africa over the period 2000-2010. First part of the paper proposes a detailed classification of host country characteristics & risks faced by an operator investing in a telecom asset in an African country, raising the awareness of the challenges facing African mobile operators. Second part includes a preliminary quantitative analysis on the correlation between license fees and host country environment. Hypothesis has been made that there is a correlation between license prices and host country indicators. Last part reminds it is necessary to have relevant license prices, so that investments amounts better reflect the characteristics and risks faced by investors on this continent. The paper highlights the importance of an accurate valuation of licenses as well as policy process in the promotion of further telecommunications investment on the continent.
Keywords: African Research